의과대학생에서 동료지지 교육이 타인돌봄과 자기돌봄 인식과 행동에 미치는 영향 - 김민경; 김혜원; Min-Kyeong Kim; Hae Won Kim (Anxiety and mood, 2025)
Objective : Peer Support, in which individuals who share common experiences provide instrumental or emotional support to each other, is a crucial resource for the well-being of medical students. However, structured training in peer support systems and research on their effectiveness is lacking. Thus, the objective of this study was to explore the effects of peer support training on medical students' perceptions and behaviors regarding care for others and self-care. Methods : This qualitative study examined the effects of peer support training based on reflective essays written by 28 medical students from a single medical school in Korea. The training included lectures, workshops, and assignments covering self-awareness, self-management, communication, and mentoring skills. A thematic analysis was performed following Braun and Clarke's model. Results : Thematic analysis identified three main themes and 10 subthemes representing changes in students' care for others and self-care. Theme 1, strengthening empathic communication skills, included three subthemes: respect for others' diverse perspectives, acquisition of active listening skills, and practice of empathic communication. Theme 2, developing mentoring-specific competencies, included three subthemes: formation of a mentee-centered mentoring attitude, enhancing self-confidence in mentoring, and understanding the limitations of mentors. Theme 3, promoting well-being through self-care, included four subthemes: understanding the importance of self-care, improving self-awareness, the practice of self-management, and the formation of new supportive relationships within the school. Conclusion : Our findings confirmed the impact of peer support training in fostering comprehensive development of care for others and self-care practices. This study highlights that peer support training can enhance students' competencies as mentors and their personal growth.